Cryogenic ion trap system for high-fidelity near-field microwave-driven quantum logic - Weber, M; Loschnauer, C; Wolf, J; Gely, MF; Hanley, R; Goodwin, J; Ballance, C; Harty, TP; Lucas, D (IOP Publishing, 2023)
We report the design, fabrication, and characterization of a cryogenic ion trap system for the implementation of quantum logic driven by near-field microwaves. The trap incorporates an on-chip microwave resonator with an electrode geometry designed to null the microwave field component that couples directly to the qubit, while giving a large field gradient for driving entangling logic gates. We map the microwave field using a single 43Ca+ ion, and measure the ion trapping lifetime and motional mode heating rates for one and two ions.